ADVANTAGES AND DISADVANTAGES OF SOLAR PANELS IN UZBEKISTAN - Makhfirat Rakhmatovna Djurayeva; Adil Tursunkulugli Rozmamatov (Galaxy International Interdisciplinary Research Journal, 2022)
The article shows how to determine the absorption efficiency levels of existing solar panels. Absorption efficiency levels of existing solar panels are based on resources and studies of useful efficiency in various environments and conditions.